Continuous Glucose Monitoring improves Diabetic Control in an Internal Medicine Residency Clinic - A. Manov; J. Tam; A. Donepudi; A. Dhaliwal; R. Haddadin; J. Badi; A. Wang; M. Sharaf; K. Mefferd (Medical Research and Its Applications Vol. 4, 2024)
In the past 3-years, a retrospective observational cohort study collected data from fifty-one patients with type 1 or type 2 Diabetes Mellitus (DM), receiving a minimum of 3-to 4 insulin injections per day, and self-monitoring their blood glucose (SMBG) 4-times a day, were derived from our internal medicine residency primary care clinic. The patients were equipped with a Continuous Glucose Monitoring (CGM) device that shared 24-hour glucose data with the clinic. The medicine resident, in consultation with our endocrinologist, assessed the patients’ glucose management data and adjusted their treatment regimens bi-weekly by calling the patients, and monthly by seeing the patients in the clinic. The rationale of the study was to show that in the Internal Medicine Residency clinic in a project governed by the medicine residents, the CGM will lead to improvement in diabetes mellitus control compared to SMBG and this can be done not only in specialized endocrine clinics. To assess for differences in A1C, TIR, average blood glucose, percent of time spent in mild hypoglycemia, and percent of time spent in pronounced hypoglycemia, five paired t-tests were conducted. A Bonferroni correction was applied which set the new accepted alpha level at 0.01. HbA1c was reduced from 9.9% to 7.6%, average blood glucose decrement from 242 mg/dL to 169 mg/dl, reduction of the incidence of mild hypoglycemia below 70 mg/dl to 54 mg/dl from 4.68% to 0.76% per day, and more pronounced hypoglycemia with glucose less than 54 mg/dl from 3.1% per day to 0.2% per day. We observed a significant increase in the time in the range of blood glucose from 33% to 67% per day. The participants were followed for 3 years. This study affirms that CGM devices significantly improved glycemic control compared to SMBG, supporting its efficacy in optimizing glycemic control in real-world clinical practice.